2015
DOI: 10.2147/oajc.s80683
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, non-use, use and source of information on contraceptive methods among women in various stages of reproductive age in rural Lagos, Southwest Nigeria

Abstract: BackgroundContraceptives are advocated to be used against unwanted pregnancy and sexually transmitted diseases as unsafe abortion contributes to high maternal mortality in Nigeria while unwanted pregnancies have terminated the educational development of many females.ObjectiveThis questionnaire-based survey aimed to describe the knowledge, nonuse, and use of various contraceptive methods among women in different child-bearing age groups in rural Lagos, Nigeria.Materials and methodsBetween 2012 and 2013, 816 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…This finding is similar to those of a mixed study among women of childbearing age from two South-Western States, Nigeria and another study from rural Lagos in which most of the respondents became aware of contraceptive methods from their antenatal clinics. [ 30 31 ] However, this result was contradicted by a community-based study among women of reproductive age in Umuahia, Abia State, in which respondents cited electronic media (television/radio) as their main source of information. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to those of a mixed study among women of childbearing age from two South-Western States, Nigeria and another study from rural Lagos in which most of the respondents became aware of contraceptive methods from their antenatal clinics. [ 30 31 ] However, this result was contradicted by a community-based study among women of reproductive age in Umuahia, Abia State, in which respondents cited electronic media (television/radio) as their main source of information. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Literature search revealed no similar study having been conducted in this geographical location in the country and extremely few in other parts similar location in sSA. The study population was defined as the homogenous group of people living together for at least 10 years at Elegushi Community in Ibeju-Lekki Local Government Area (LGA) and Ijede Community at Ikorodu LGA of Lagos State, Nigeria (Afolabi et al, 2015). In general there was a high literacy rate of 88.4% in Lagos State and 91.6% among those aged 15 to 49 years (NPC, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…1,20 Information sources also play a role in contraception uptake. [22][23][24] In our study, medical personnel were the most frequently reported source of information about contraception, over neighbours, radio or television, and the Church. In rural Malawi, it has been shown that the media can play a significant role in improving maternal health outcomes when it is community-led and locally driven.…”
Section: Discussionmentioning
confidence: 79%